Indonesia's Constitutional Court: Bastion of Law Enforcement and Protector of Human Rights in The Reform Era - Pujayanti, Luh Putu Vera Astri; Nugrahayu, Zainun Zakya; Rahim, Erman I.; Muhtar, Mohamad Hidayat; Yassine, Chami (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
This study aims to analyze the role of the Indonesian Constitutional Court in carrying out its function as a stronghold of law enforcement in Indonesia after the reform era, as well as evaluate the extent to which this institution has succeeded in protecting human rights through its decisions. Methods: This research is categorized as normative legal research with a philosophical and analytical approach. The focus is on rational, critical, and philosophical analysis of the legal issues raised. The analytical descriptive method is used to describe the applicable legislation, legal theory, and positive law enforcement practices related to the problem under study. Results: The results show that the Indonesian Constitutional Court plays an important role in upholding the Constitution and social justice with a careful and balanced approach. Key decisions such as No. 18/PUU-V/2007, No. 75/PUU-XIII/2015, and No. 102/PUU-XXI/2023 highlight the importance of legislative autonomy, legal clarity, and certainty, as well as the presumption of innocence and prudence in political intervention. The application of Aharon Barak's theory of "proportionality," Lon Fuller's "legal certainty," and Alexander Bickel's "judicial restraint" provides insight into ensuring a balance between human rights, legal certainty, and the integrity of due process.